The importance of transfer attributes in public transport passengers’ route choice - Eltved, Morten; Nielsen, Otto Anker; Anderson, Marie Karen (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
This study provides insight into how passengers value transfer facilities compared to other components of a route when choosing their route in public transport. A thorough analysis of previously estimated parameters for public transport route choice and a selection of the best available data for describing passenger preferences for transfer attributes led to a short list of three variables, which elaborates the general transfer penalty often included in route choice models in public transport. These are shopping availability, number of escalators at transfer stations and the difficulty of wayfinding at transfers. Shopping availability and the number of escalators improve the passengers’ utility of a certain route while more difficult wayfinding at transfer points have a negative impact on the utility of a route. The effect of the additional transfer attributes in the model is in general only significant for trips with work related purposes (commuting and business trips). The more detailed route choice model including transfer attributes makes it possible to evaluate the effect of different station designs and improvements of existing station facilities.